Phenomenology of Wedding Communication in Different Countries (Indonesia's Cultural Wedding with A Swedish Man) - Nurrahmi Nurrahmi; Jupendri Jupendri; Sumaiyah Sumaiyah; Fatiha Maharani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Cross-cultural communication in marriage involves understanding and adapting to the different norms, values, and traditions between partners from different cultures. Addressing differences in language, attitudes, and expectations is essential to establish effective communication, build trust, and minimize conflicts. This study aims to explore cross-cultural communication in interethnic marriages in Sweden. Data collection techniques included observation, interviews, and documentation. The informants were married couples from different countries: a woman from Indonesia and a man from Sweden. The research method used was descriptive qualitative with a phenomenological approach, and the researcher connected the research object to Face Negotiation Theory. The results showed that the couple from two different countries tended to avoid conflict and displayed cooperative attitudes (obliging) in responding to differences and conflicts arising in daily interactions. Consequently, a harmonious marital relationship was established.